Sierra Leone : 2022 Article IV Consultation and Fifth Review under the Extended Credit Facility Arrangement, Requests for Waivers of Nonobservance of Performance Criteria, Modifications of Performance Criteria, and Financing Assurance Review-Press Release; Staff Report; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report, 2022)
Sierra Leone continues to pursue its development path amidst continued vulnerability to shocks and still fragile institutions. Despite a decisive health and economic response to the COVID-19 pandemic, less than one in five Sierra Leoneans is vaccinated, and urgent challenges, such as food insecurity, persist. The authorities' ambitious National Development Plan is showing first results in the education sector, but human development outcomes remain among the weakest worldwide. The COVID-19 crisis and the war in Ukraine has stoked inflation and exacerbated an exceptionally tight fiscal situation in the context of high risk of debt distress, severely limiting the authorities' room to maneuver.